Interactive challenges in online student participatory language learning through closed social network / Liaw Shun Chone, Rasaya A/L Marimuthu and Mohaiyedin Idris - Liaw, Shun Chone; Marimuthu, Rasaya; Idris, Mohaiyedin (Universiti Teknologi MARA, Kedah, 2014)
Learning does not take place in a vacuum. According to Cottone (2001), learning is an interactive rather than an individual process. It involves exchanging of ideas, negotiating and sharing of decision making together. It is a far cry from the classroom situation in the past when the all-knowing lecturer provided details to the students who then merely imbibed the knowledge in wholesomely and unquestionably. The paradigm shift in learning has encouraged students from just being passive learners into becoming active participants responsible for their own acquisition of knowledge while lecturers now take a backseat and act only as facilitators to oversee progress made by their students. Through such online learning, students interact with group members to learn from each other and also from their lecturers when the need arises. Similarly, online learning in language courses has seen students engaging themselves in language tasks. There is no denying the benefits accrued from students’ online collaborative activities (Roberts,2005) and in the expansion of students’ opportunities in distance learning ( Schrum, 2000). However, lecturers need to initiate studies on how its online learning beyond classroom context has hindered satisfactory participation of students in online language courses through closed social network.